Characteristic and non-characteristic harmonics from windparks - Yang, Kai; Bollen, Math; Wahlberg, Mats (Luleå tekniska universitet, Energivetenskap, 2011)
This paper presents measurements of harmonic current emissions up till 2 kHz from four different windparks in northern Sweden, all equipped with modern power-electronics converters. A study of the four windparks was performed interms of 95% value of harmonic current spectrum and the minimum fault-level needed to fulfil the EN 50160 requirements on voltage distortion. The results show that there exists different dominating harmonics and fault-level requirements for different windturbines. Each turbine however shows a broadband component with superimposed narrowband components. The impact on the grid, with reference to permissible levels of voltage distortion, is biggest for the interharmonic components. Validerad; 2011; 20110818 (andbra)